PEMBERIAN ABU SERBUK GERGAJI DAN PUPUK UREA, TSP, KCl TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annuum L.) DI LAHAN GAMBUT - Raziliano '; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to determine effect of sawdust ashes combined with urea, TSP, KCl on the growth and yield of chilli (Capsicum annuum L.) on peat land. This research was conducted on May 2014 until August 2014 in the experimental garden of peatland Agriculture faculty of University of Riau, Rimbo Panjang Village, Tambang District, Kampar. Research was conducted experimentally using Randomized Block Design (RBD) factorial 3x3. Each treatment was repeated 3 times to obtain 27 experimental units. Each experimental unit consisted of 14 plants and five plants was taken as a sample plants. The first factor consists of 3 levels and the second factor is Urea + TSP + KCl (P) fertilizer consists of 3 levels. Oberserved parameters were the plant height, days to flowering, days to harvesting, fruit weight per plant, fruit weight per plot, fruit length, fruit diameter and number of fruits per-plant samples. Data were analyzed by ANOVA and further tested using Duncan`s New Multiple Range Test (DNMRT) at the level of 5%. The results shows giving sawdust ashes and urea, TSP, KCl fertilizer influenced on the plant height, fruit length, stem diameter, fresh fruit weight per-plant and fresh fruit weight per-plot. Giving sawdust ashes with dose of 12 kg/plot and urea 100 g/ plot, TSP 200 g/ plot, KCl 160 g/plot is the best dose in enhancing growth and production of chilli plants in peatland. Keywords: chilli, peatland, sawdust ashes